Percutaneous drainage of a parotid gland abscess under contrast-enhanced ultrasound guidance: A case report. (August 2018) - Scattergood, Sean; Moore, Stephen; Prior, Andrew; Yusuf, Gibran T; Sidhu, Paul S
A parotid gland abscess is uncommon and if not responding to conservative management, requires surgical intervention. However, surgery is invasive with the risk of complicating facial nerve damage and possible poor cosmetic outcome. We present a case of a parotid gland abscess in association with an underlying Warthin's tumour requiring percutaneous drainage, as patient co-morbidity precluded a safe surgical approach. Percutaneous drainage was aided by a contrast-enhanced ultrasound examination, which permitted delineation of the fluid aspects of the collection from the underlying tumour and allowed successful percutaneous ultrasound-guided aspiration without complication.